2023
DOI: 10.1007/s00256-022-04259-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the differences between radiographic joint space width and MRI cartilage thickness changes using data from the IMI-APPROACH cohort

Abstract: Objective Longitudinal weight-bearing radiographic joint space width (JSW) and non-weight-bearing MRI-based cartilage thickness changes often show weak correlations. The current objective was to investigate these correlations, and to explore the influence of different factors that could contribute to longitudinal differences between the two methods. Methods The current study included 178 participants with medial osteoarthritis (OA) out of the 297 knee OA participants enrolled in the IMI-APPROACH cohort. Change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Also, the current study revealed that the different progressor definitions do not show a high agreement ( Tables S3-S5 ), which may explain why the s-score cannot be reused to predict other progression definitions as well. In the comparison between JSW and MRI cartilage thickness this could potentially be the result of differences in acquisition (such the difference in weight-bearing, or the fact that JSW progression is a composite result of cartilage loss and meniscal damage and extrusion) ( 27 ), but even progression on qMRI cartilage thickness and MOAKS cartilage scores showed only low agreement in this study. This means that, even if the progression in one parameter (in this case minimum JSW) could have been predicted perfectly, this would not necessarily have resulted in a similarly high number of progressors in the other structural parameters.…”
Section: Discussionmentioning
confidence: 65%
“…Also, the current study revealed that the different progressor definitions do not show a high agreement ( Tables S3-S5 ), which may explain why the s-score cannot be reused to predict other progression definitions as well. In the comparison between JSW and MRI cartilage thickness this could potentially be the result of differences in acquisition (such the difference in weight-bearing, or the fact that JSW progression is a composite result of cartilage loss and meniscal damage and extrusion) ( 27 ), but even progression on qMRI cartilage thickness and MOAKS cartilage scores showed only low agreement in this study. This means that, even if the progression in one parameter (in this case minimum JSW) could have been predicted perfectly, this would not necessarily have resulted in a similarly high number of progressors in the other structural parameters.…”
Section: Discussionmentioning
confidence: 65%
“…However, the minJSW measurement reflects a one-dimensional thickness measured from one specific location of the joint, and it may also include other tissues such as the menisci [21]. A correlation analysis between cartilage thickness and minJSW from previous studies showed some variation between the two parameters, which was explained by variation in the cartilage thickness [22,23]. The C2M levels in serum were also found to be negatively correlated with KL grade.…”
Section: Relationship Between Biomarkers' Levels and Structural Outco...mentioning
confidence: 95%